IMPLEMENTASI PENGGUNAAN SURVEY DIGITAL PADA RISET KEBERLANJUTAN UMK MAKANAN DAN MINUMAN DI KECAMATAN GUBENG - Nugraha, Dwiki Andreansyah; Ignatia Martha Hendrati; Wirya Wardaya (Institute for Research and Community Services, 2024)
This service project aims to empower Micro and Small Enterprises (MSEs) in Gubeng District through the implementation of digital surveys. The primary objective of the project was to enhance research and data collection efficiency through the utilization of information technology, specifically by employing the CAPI survey method. The project included the creation of a tailored digital survey with the specific purpose of assessing the sustainability dimensions of the MSEs. This survey covered various factors such as products, service, management, digital aspects, and the role of the government. In addition, the project also aimed to conduct a digital survey to the respondents regarding the advantages of digital surveys. The use of a digital survey platform facilitates wider participation and makes it easier to collect data directly. The obtained data were statistically and qualitatively analyzed to produce a comprehensive insight into the sustainability dynamics of MSEs in the Gubeng Sub-district within the food and beverage sector. The advantages of implementing a digital survey include time, cost, and resource savings, as well as making it possible for researchers to achieve a more representative sample. The project's outcomes are expected to offer a comprehensive perspective on the sustainability prospects of Micro and Small Enterprises (MSEs) within the food and beverage industry. In addition, these results aim to offer insights to stakeholders involved in crafting policies and support initiatives.